Siren queen [large type] - Vo, Nghi (THORNDIKE PRESS LARGE PRINT Basic, 2022)
"It was magic. In every world, it was a kind of magic. "No maids, no funny talking, no fainting flowers." Luli Wei is beautiful, talented, and desperate to be a star. Coming of age in pre-Code Hollywood, she knows how dangerous the movie business is and how limited the roles are for a Chinese American girl from Hungarian Hill--but she doesn't care. She'd rather play a monster than a maid. But in Luli's world, the worst monsters in Hollywood are not the ones on screen. The studios want to own everything from her face to her name to the women she loves, and they run on a system of bargains made in blood and ancient magic, powered by the endless sacrifice of unlucky starlets like her. For those who do survive to earn their fame, success comes with a steep price. Luli is willing to do whatever it takes--even if that means becoming the monster herself. Siren Queen offers up an enthralling exploration of an outsider achieving stardom on her own terms, in a fantastical Hollywood where the monsters are real and the magic of the silver screen illuminates every page"--